Implementation of the Division of Joint Assets Based on a Notarial Deed Due to Divorce - Salsabila, Amalia Rifdah (TABELLIUS: Journal of Law, 2023)
This research aims to find out and analyze the implementation of knowing and analyzing the implementation of the distribution of joint assets based on notarial assets resulting from divorce and the basis of the judge's consideration in deciding cases regarding the distribution of joint assets due to divorce as well as analyzing the relationship between the notary's deed and the judge's decision which has decided on the division of joint assets due to divorce. In researching and preparing this thesis, the author used normative juridical research methods. The Normative Judicial Approach is research that refers to existing literature studies or secondary data. Meanwhile, Normative is Legal Research which aims to obtain Normative Knowledge about the Relationship between one Regulation and another Regulation and its Application in Practice. The type of data used secondary types, namely data obtained from or originating from library materials, secondary data collected in this research includes primary legal materials, secondary legal materials and tertiary legal materials. There are no similarities or differences between the distribution of joint property determined by a Notary and the Religious Court Judge's Decision, but rather similarities, because the deed made by the notary has definite legal force and the deed used as evidence is an authentic deed, which provides evidence that perfect regarding what is contained therein. Because the court makes a reference or basis for making decisions so that disputes or problems do not occur in the future. Keywords: Collective; Courts; Notaries; Religious; Rights.